A handbook of Environmental Quality Index / Shawal Sahid Hamid @ Hussain, Noorliana Safian and Nur Khairunnisa Liyana Ahmad - Hamid @ Hussain, Shawal Sahid; Safian, Noorliana; Ahmad, Nur Khairunnisa Liyana (2021)
Environmental Quality Index (EQI) represents four domains of the environment: air, water, noise and light. This index is significant in translating a wide variety of environmental indicators into a simple system that can easily be communicated. Based on a survey carried out to 50 students of EVA631 with regards to their learning difficulties, it was found out that, one of the major problems on their learning is difficulties to access to various environmental indexes during classes. Furthermore, to date, there is an absence of a handbook that compiles the index of all the quality domains. Therefore, this handbook aims to provide an easy quick reference to the students in referring to various EQI. In order to better understand students’ perceptions towards this handbook, a survey was carried out towards 50 students of EVA631 and the findings reveal that, overall, students were satisfied with the content of the handbook. With this innovative idea, it is hoped that students will be able to be more focused on their learning especially in the era of the Covid-19 pandemic.